Clinical scenarios-based guide for tofacitinib in rheumatoid arthritis - Mahta Mortezavi; Eduardo F. Mysler (SAGE Publishing, 2023)
Tofacitinib was the first Janus kinase inhibitor to be approved for the treatment of rheumatoid arthritis (RA), and there is a large body of data to inform the efficacy and safety of this drug for patients at different places in their treatment journeys and with diverse demographics and characteristics. Here, we summarize tofacitinib clinical efficacy and safety data from some clinical trials, post hoc analyses, and real-world studies, which provide evidence of the efficacy of tofacitinib in treating patients with RA at various stages of their treatment journeys, and with differentiating baseline characteristics, such as age, gender, race, and body mass index. In addition, we review the safety data available from different patient subpopulations in the tofacitinib clinical development program, real-world data, and findings from the ORAL Surveillance post-marketing safety study that included patients aged ⩾50 years with pre-existing cardiovascular risk factors. The available efficacy and safety data in these subpopulations can enable better discussions between clinicians and patients to guide informed decision-making and individualized patient care.